INTEGRATED WEB-BASED DATA WAREHOUSE AND ARTIFICIAL NEURAL NETWORKS SYSTEM FOR UNIT PRICE ANALYSIS WITH INFLATION ADJUSTMENT - Baalousha, Yousef; Celik, Tahir (Vilnius Gediminas Tech Univ, 2011)
Estimating is a fundamental part of construction projects. Accurate cost estimate is the single most important element involved in the series of events that leads to a profitable completion of a contract in construction industry. The success or failure of a project depends on the accuracy of cost estimation. A cost estimate becomes more difficult and more complicated under inflationary medium. An unpredictable inflation rate and long progress payment delay during this period makes the budgeting function very difficult, if not impossible. The cost estimation process uses lots of data. The availability of the appropriate data at the appropriate time is one of the main factors affecting the accuracy of the cost estimation. As the complexity of the estimating task increases computerized system becomes increasingly important. The estimator should develop a good system of estimating forms and procedures that exactly meet the requirements of the project, and that is understood and accessible by all team members. This system should provide the ability to define material, labor hour and equipment hour quantities required for the project. Material, labor, and equipment unit costs are then applied to the bill of quantities. This paper presents An Integrated Web-Based Data Warehouse and Artificial Neural Networks Model for Unit Price Analysis with Inflation Adjustment system called DANUP. Web facilities and database management capabilities of Microsoft Visual Studio 2005 are applied to create a data warehouse which is mainly aimed to integrate data from multiple heterogeneous databases and other information sources. The System also supports integrated cost index for adjusting the effect of inflation during estimating process. An artificial neural network model for forecasting the cost indices in Turkey for the project period has been developed. A construction project takes relatively long time to complete, effective communication among the project participants during the project period is important. A web based system is developed to facilitate the collection of construction cost information and communication. The web based system focuses on demonstrating the potential of data centric web data bases in enhancing the communication process during project execution. End users can access the database through the interne and perform certain transactions according to their authorization.
Keywords: web data warehouse; unit price analysis; artificial neural networks; inflation; MATLAB